THE STRUCTURE OF SOCIAL REPRESENTATIONS OF ASSESSMENT AMONG PRE-SERVICE EARLY CHILDHOOD EDUCATORS - Coppi, Marcelo; Fialho, Isabel; Saragoça, José (Revista Prâksis, 2026)
This study aimed to analyze the structure and meanings of social representations (SR) of assessment in pre-service early childhood educators, identifying and interpreting their central core and peripheral system. Adopting a qualitative and exploratory approach within the structural framework of the Theory of Social Representations (TSR), the investigation involved 30 first-year students from the master’s programs in Preschool Education and Preschool Education and Primary Education at the University of Évora. The free word association technique (FWAT) was administered with the inducing term assessment, followed by hierarchization and justification of the evocations. The data, lemmatized and processed, were subjected to multiple frequency, prototypical, and similitude analyses using IRaMuTeQ software. The results revealed coherent SR centered on the element learning, reflecting a formative perspective of assessment, associated with a continuous process of monitoring and support for child development, fundamental for informing and regulating pedagogical practice. In summary, the pre-service early childhood educators internalized a conception of assessment deeply aligned with contemporary paradigms of assessment for learning.